Estrategias de comercialización del queso el SINCHE de la hacienda el Sinche, parroquia Guanujo, cantón Guaranda, año 2014.” - Guevara Salazar, Gloria Celina (2015)
The hacienda Sinche via the Salinas de Bolivar, located in the Sinche community, parish Guanujo, Canton Guaranda, Province of Bolivar; dedicated to the production of cheese of the same name "The Sinche" which offer the product in smaller amounts within the city and to a greater extent beyond, reflecting very low power consumption due to the lack of marketing strategies that contribute to improve sales within the city of Guaranda. So we feel that conducting a study on the ranch is feasible to identify problems and get the causes of them: through research we conducted an analysis of the current situation and then gathering information through interviews and surveys conducted the owner, workers and consumers; with the opening provided by the owner and whether the support of all staff is made the same, as well as information for scientific theory obtained from books, web pages on the issue raised, which will allow the development of the draft as provided in the regulations graduation from the Faculty of Administrative Sciences, Management and Informatics State University of Bolivar. The development of the proposal is all the information collected from the farm the Sinche. Making a Marketing Strategy Plan according to the market where it is to increase product sales, the same will be announced at the ranch and everyone involved will make a continuous monitoring to thereby verify compliance with the objectives raised, allowing improve the Sinche cheese marketing within the city of Guaranda.